THE IMPLEMENTATION OF MANDATORY OR VOLUNTARY FOR CORPORATE SOCIAL RESPONSIBILITY: A SYSTEMATIC LITERATURE REVIEW - Putri, Cut Nurul Tasya; Masse, Finka Azzahra Utami; Kesuma, Sambas Ade (jfpublisher, 2023)
CSR (Corporate Social Responsibility) is the responsibility of a company for the impact of their decisions and activities on society and the environment through open and ethical behavior. The existence of companies in the midst of society contributes to the national problem of unemployment. The implementation of CSR in Indonesia is still not transparent whether it is voluntary or mandatory. However, this research does not only discuss the Indonesian side, but globally in several countries from 2007-2023. Therefore, this research aims to find out the implementation of mandatory or voluntary CSR in Indonesia and some countries. The method used is systematic literature review. The result of this research is voluntary CSR is still commonly used in various countries, including developing countries, even though some countries have regulated mandatory CSR by law. However, voluntary CSR is still practiced because the law is not enough for companies to implement mandatory CSR. Companies will be more stable if they implement mandatory and voluntary CSR in a balanced way in order to consider the interests of stakeholders, the company, the environment and society.